La réparation du préjudice écologique en Espagne, l’affaire du Prestige - Albert Ruda González (VertigO)
This paper focuses on the approach adopted by Spanish law as regards oil spill pollution, in particular in the aftermath of the Prestige accident. The author analyses the legal response to this kind of catastrophes from a domestic and international perspective and inquires whether natural environment is sufficiently protected.